Pengaruh Kebijakan Pemerintah Dan Harga Pada Keputusan Pembelian Jasa Penyelenggara Kursus Dengan Iklan Sosial Media Sebagai Variabel Mediasi Pada Lembaga Kursus Texas College Kota Metro - Sri Retnaning Rahayu; Ratmono; Hafidz Bahtiar (Universitas Muhammadiyah Metro, 2024)
The research was based on the fact that the number of new students registering for TexasCollege courses experienced ups and downs from 2018 to 2021 due to the increase in pricesfor each course level over the last four years. If this continues continuously it will have animpact on student interest. The purpose of this research is to determine the influence ofgovernment policies and prices on purchasing decisions for course provider services withsocial media advertising as a mediating variable at the Texas College Metro Course Institute.This research is quantitative research. With this type of explanatory survey research, thesampling technique was purposive sampling, as many as 75 students from LKP Texas CollegeMetro. As a measuring tool, an 80-item questionnaire was used with Likert scalemeasurements and analyzed using Path Analysis. The research results show that governmentpolicy has a positive effect on service purchasing decisions. Price has a positive effect onservice purchasing decisions. Social media advertising has a positive effect on servicepurchasing decisions. Government policies have a positive influence on social mediaadvertising. Price has a positive effect on social advertising. Government policies have apositive influence on service purchasing decisions through social media advertising. Pricehas a positive influence on service purchasing decisions through social media advertising.